Perturbation of the heparin/heparin-sulfate interactome of human breast cancer cells modulates pro-tumourigenic effects associated with PI3K/Akt and MAPK/ERK signalling - Chen, Yunliang; Scully, Michael; Dawson, Gloria; Goodwin, Christopher; Xia, Min; Lu, Xinjie; Kakkar, Ajay (Thrombosis and Haemostasis, 2013)
Heparansulfate-proteoglycans (HSPGs) interact via their polyanionic heparansulfate (HS) side chains with a variety of proteins on the cell surface or within the extracellular matrix membrane. The large number of heparin/HS binding proteins form a highly interconnected functional network, which has been termed as the heparin/HS interactome and is functionally linked to physiological and pathological processes. The aim of this study was to investigate the global effect of these protein-HSPG interactions on the tumourigenicity of two breast cancer cell lines (MCF-7 and MDA-MB-231). Cancer cells were cultured in serum-free medium and treated with a concentration of heparin which was capable of modulating HS/ligand interaction. Microarray analysis of MCF-7 cells cultured under these conditions showed that expression of 105 of 1,357 genes potentially related to the pathogenesis of breast neoplasm was significantly altered by heparin treatment. The changes in gene expression correlated with a less tumourigenic phenotype, including reduction of cell adhesive, invasive and migratory properties. These effects were associated with an inhibition of the PI3K/Akt and Raf/MEK/ERK signalling pathways. The modulatory effect of heparin on HS-associated activity was confirmed with one example of heparin/HS interactomes, transforming growth factor β (TGFβ). The innate TGFβ activity of MCF-7 cells was reduced by heparin treatment, with specific interruption of the TGFβ–Smad signalling pathway. The pro-tumourigenic contribution of the heparin/HS interactomes was verified in cells in which HSPG synthesis was blocked using β-xyloside. In conclusion, the interaction between cell surface HPSGs and innate heparin/HS interactomes makes a significant contribution to the tumourigenicity.
Keywords: Heparin/heparan sulfate interactomes; breast cancer cell; tumourigenicity